Cysteine-524 is not the only residue involved in the formation of disulphide-bonded dimers of the insulin receptor. - Macaulay, S L (1994)
The human insulin receptor (hIR) is a member of the transmembrane tyrosine kinase receptor family. It is a disulphide-linked homodimer which can be reduced to two insulin-binding monomers by mild reduction of class-I disulphide bonds. The number of disulphide bonds between the alpha- and beta-chains within the monomer or between the monomers in the dimer is not known, although one dimer bond involving hIR Cys-524 has recently been identified [Schaffer and Ljungqvist (1992) Biochem. Biophys. Res. Commun. 189, 650-653]. In the present report hIR Cys-524 was converted into alanine by site-directed mutagenesis and expressed at high levels in Chinese hamster ovary (CHO) cells. The mutant receptor was processed normally and shown to bind insulin normally, with ED50 and KD values not different from those of the wild-type hIR. It was still a disulphide-linked dimer as judged by SDS/PAGE, indicating that there are alpha-alpha-chain disulphide bonds additional to the Cys-524 linkage in the insulin receptor dimer. Insulin-stimulated receptor autophosphorylation and kinase activity of the mutated receptor were both impaired compared with that of the wild-type receptor by 49% and 53% respectively. CHO cells overexpressing the mutant receptor, however, did not show a reduced capacity to stimulate glucose utilization, indicative that the level of receptor expression was sufficient to saturate downstream insulin action. These findings indicate that alpha-alpha disulphides additional to that provided by Cys-524 hold the receptor dimer together and that mutagenesis of Cys-524 reduces the ability of the receptor to signal insulin action subsequent to hormone binding.